Extraction of stevia glycosides with CO2 + water, CO2 + ethanol, and CO2 + water + ethanol - Pasquel,A. (2000)
Stevia leaves are an important source of natural sugar substitute. There are some restrictions on the use of stevia extract because of its distinctive aftertaste. Some authors attribute this to soluble material other than the stevia glycosides, even though it is well known that stevia glycosides have to some extent a bitter taste. Therefore, the purpose of this work was to develop a process to obtain stevia extract of a better quality. The proposed process includes two steps: i) Pretreatment of the leaves by SCFE; ii) Extraction of the stevia glycosides by SCFE using CO2 as solvent and water and/or ethanol as cosolvent. The mean total yield for SCFE pretreatment was 3.0%. The yields for SCFE with cosolvent of stevia glycosides were below 0.50%, except at 120 bar, 16°C, and 9.5% (molar) of water. Under this condition, total yield was 3.4%. The quality of the glycosidic fraction with respect to its capacity as sweetener was better for the SCFE extract as compared to extract obtained by the conventional process. The overall extraction curves were well described by the Lack extended model.